Influence of External and Situational Stimulus Factors on Impulse Buying : A Stimulus-Organism- Response Framework - Sen, Shaon (Indian Journal of Marketing, 2024)
Purpose : This study aimed to develop a research model that incorporated the cognitive (useful) and affective (hedonic) motivations that influence the relationship between external and situational stimuli on consumers’ impulsive buying while adopting the stimulus-organism-response (S-O-R) framework. The study has proposed a number of situational and external cues that, through the customers’ affective and cognitive incentives, stimulate their impulsivity toward purchasing. Methodology : This study extensively reviewed scholarly research works published in national and international peer-reviewed journals published between 2012 and 2024 identified through specific keyword searches and iterative search results. Henceforth, this study excluded the research articles that did not comply with the relevance and the search criteria. All the research articles considered for the literature review are written in English. Findings : This study used a direct antecedent-consequent link to provide a thorough explanation of the phenomenon of impulsive buying. It has discussed how buyers’s cognitive and affective emotions play a role in what leads to their impulsive purchasing behavior. Practical Implications : The propositions would assist marketers in unveiling the enigma of the consumers’ need recognition that is often triggered by consumers’ trait changes due to psychological shifts; henceforth, practitioners would design effective marketing communications. Originality : This research is distinct from previous studies since it used the S-O-R paradigm and included a mediation role for affective and cognitive emotions in order to try and resolve the current disagreement among researchers regarding the influence of peer pressure on impulsive buying behavior.